The Role of ESG Criteria in Sustainable Financial Project Scope Management: A Systematic Literature Review - Martino Wibowo; Heri Setiawan; Dwi Dewianawati; Erry Setiawan; Loso Judijanto (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In the era of sustainable development, financial scope management increasingly demands the integration of environmental, social, and governance criteria to ensure long-term project viability and resilience. This study examines how incorporating environmental, social, and governance dimensions enhances project sustainability and strengthens responses to global economic, social, and environmental challenges. A qualitative approach was employed, using a systematic literature review of publications and professional reports from 2019 to 2024, with content analysis to identify trends and patterns in environmental, social, and governance adoption within financial project management. Findings reveal that environmental, social, and governance integration improves project accountability, reduces non-financial risks such as climate change and social inequality, and shifts evaluation from short-term profitability to long-term sustainability. The study contributes to theory by providing a conceptual framework for sustainable financial scope management that positions environmental, social, and governance as a strategic, rather than administrative, consideration across the project lifecycle. It offers actionable guidance for managers, policymakers, and project stakeholders on designing financial projects that are responsible, transparent, and resilient, emphasizing adaptive governance, risk mitigation, and stakeholder engagement. These insights support the development of more sustainable investment practices and reinforce the strategic role of environmental, social, and governance in financial decision-making.